Protean and boundaryless career attitudes: relationships with subjective and objective career success - Judith Volmer; Daniel Spurk (Zeitschrift für ArbeitsmarktForschung - Journal for Labour Market Research, 2011)
The protean and boundaryless career attitudes have gained special attention during the past years. A protean career attitude implies that a person strives towards a developmental progression and self-fulfillment; a boundaryless career attitude is characterized by a high physical and/or psychological mobility. The aim of the present paper is twofold: First, we want to empirically investigate the relationship between protean and boundaryless career attitudes and subjective (i.e., career satisfaction and success in comparison with colleagues) and objective (i.e., promotions and salary) career success. Second, we want to integrate research on protean and boundaryless career attitudes with research on predictors of career success. We analyze the career attitudes-career success relationship with a sample of 116 professionals. Our findings suggest that components of the protean career attitude are rather more related with subjective career success and that components of the boundaryless career attitude are more related with objective career success. Conclusions regarding the relevance of career attitudes for career success are drawn.
Keywords: J30; J60; 330; Berufserfolg; Berufszufriedenheit; Arbeitszufriedenheit; Einkommen; Leistungsmotivation; Aufstiegsmotivation; soziale Mobilität; zwischenbetriebliche Mobilität; beruflicher Aufstieg; Beförderung; Mobilitätsbereitschaft; Arbeitskräfte - Einstellungen; multinationale Unternehmen